Circulating Endothelial Microparticles Reduce in Concentration Following an Exercise Programme in Women With Polycystic Ovary Syndrome - Kirk, Richard J.; Madden, Leigh A.; Peart, Daniel J.; Aye, Myint M.; Atkin, Stephen L.; Vince, Rebecca V. (Frontiers in Endocrinology, 2019)
Purpose: Endothelial dysfunction is a known comorbidity in women with polycystic ovary syndrome (PCOS). The aim was to assess if supervised, moderate intensity exercise could potentially impact markers of endothelial disruption; endothelial cell derived microparticles (EMP). Methods: The current study investigated the effects of a supervised 8-week moderate intensity exercise programme on EMP in women with PCOS (n=11) and control women free from any known disease (n=10). EMP were enumerated via specific antibody (CD105, CD106) labelling and flow cytometry. Results: CD105+MP significantly reduced in women with PCOS from pre to post exercise programme, with CD105+ MP reducing from 2114 CD105+ MP per µl platelet free plasma (PFP) to 424 CD105+ MP per µl PFP (p = 0.025). Control women showed no significant change in CD105+ MP (p = 0.25) after completing the same exercise programme. CD106+ MP showed no change in either PCOS (p = 0.95) or control groups (p = 0.99). No significant correlations existed with the changes in endothelial microparticles (EMP) compared to body composition changes as a result of exercise. Conclusion: Supervised, moderate intensity exercise independent of substantial weight loss reduced circulating CD105+MP, likely reflecting an improvement in endothelial function in women with PCOS compared to healthy control women. Additionally, EMP may be a useful marker for physical improvement in exercise programmes for clinical populations.